Employability strategies and the search for Decent Work in peruvian archaeology - Silva Pardavé , Daniela R. (2025)
In Peru, education in archaeology marginally addresses the labor market and working conditions. Given this situation, a diagnosis of the national labor scenario was carried out with the objectives of identifying strategies adopted by professionals between 23 and 40 years of age to guarantee their employment, and recognizing the factors that undermine Decent Work. Consequently, a self-administered survey was issued to the population of actively working archaeologists. Additionally, six professionals from the same population segment were interviewed. The results show that professional licensing, volunteer work, development of soft skills and professional networks, as well as a solid academic education favor insertion and job performance, while bad professional practices, restricted job offers, discrimination and violence, the precarious nature of employment contracts, infringement of the work schedule, and the absence of an influential labor union or association are the factors that hinder Decent Work in archaeology.